The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2012
DOI: 10.1002/asia.201200231
|View full text |Cite
|
Sign up to set email alerts
|

Interconversion of Metallabenzenes and Cyclic η2‐Allene‐Coordinated Complexes

Abstract: Treatment of the osmabenzene [Os{CHC(PPh(3))CHC(PPh(3))CH}Cl(2)(PPh(3))(2)]Cl (1) with excess 8-hydroxyquinoline produces monosubstituted osmabenzene [Os{CH C(PPh(3))CHC(PPh(3))CH}(C(9)H(6)NO)Cl(PPh(3))]Cl (2) or disubstituted osmabenzene [Os{CHC(PPh(3))CHC(PPh(3))CH}(C(9)H(6)NO)(2)]Cl (3) under different reaction conditions. Osmabenzene 2 evolves into cyclic η(2)-allene-coordinated complex [Os{CH=C(PPh(3))CH=(η(2)-C=CH(2))}(C(9)H(6)NO)(PPh(3))(2)]Cl (4) in the presence of excess PPh(3) and NaOH, presumably in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 106 publications
1
9
0
Order By: Relevance
“…The Os1=N1 bond length (1.806(10) Å) is within the typical range of bond lengths for azavinylidene–osmium complexes (1.777–1.881 Å), and the N1=C4 bond length (1.261(15) Å) is in the expected range for C=N double‐bond lengths. The Os1−C1 (2.095(11) Å) and C1=C2 (1.350(16) Å) bond lengths are similar to those found in other osmium–vinyl metallacycles and support the presence of a vinyl moiety. In contrast to the metallacycles in 2 a and 3 a , that in complex 4 a clearly deviates from planarity, which is reflected by the sum of the angles in the six‐membered ring (713.4°).…”
Section: Resultssupporting
confidence: 73%
“…The Os1=N1 bond length (1.806(10) Å) is within the typical range of bond lengths for azavinylidene–osmium complexes (1.777–1.881 Å), and the N1=C4 bond length (1.261(15) Å) is in the expected range for C=N double‐bond lengths. The Os1−C1 (2.095(11) Å) and C1=C2 (1.350(16) Å) bond lengths are similar to those found in other osmium–vinyl metallacycles and support the presence of a vinyl moiety. In contrast to the metallacycles in 2 a and 3 a , that in complex 4 a clearly deviates from planarity, which is reflected by the sum of the angles in the six‐membered ring (713.4°).…”
Section: Resultssupporting
confidence: 73%
“…148,149,454 Similar substitution reactions have also been found in osmabenzenes. 134,136,455 Moreover, Xia et al found that, when L-cysteine was added into an aqueous solution of 473 at physiological pH 7.4, two diastereomeric isomers (Λ Ru , R C )-474 and (Δ Ru , R C )-474 were generated. From the results of CD (circular dichroism) spectroscopy, NMR spectroscopy, and X-ray crystal structures, the authors speculated that (Λ Ru , R C )-474 is the thermodynamic product, while (Δ Ru , R C )-474 is the kinetic product, and the ratios are dependent on the pH values (Scheme 151).…”
Section: Reactivities Of Metallabenzenesmentioning
confidence: 99%
“…466 Such reactions were further extended to an osmabenzene. 455 Intramolecular nucleophilic substitution reactions have also been reported. For example, when complex 29 was treated with NaOMe, osmabenzothiazole 515 was isolated.…”
Section: Electrophilic Substitution Of Metallabenzenesmentioning
confidence: 99%
See 2 more Smart Citations